JMJD8 Is an M2 Macrophage Biomarker, and It Associates With DNA Damage Repair to Facilitate Stemness Maintenance, Chemoresistance, and Immunosuppression in Pan-Cancer - Liang, Xisong; Zhang, Hao; Wang, Zeyu; Zhang, Xun; Dai, Ziyu; Zhang, Jian; Luo, Peng; Zhang, Longbo; Hu, Jason; Liu, Zaoqu; Bi, Changlong; Cheng, Quan (Frontiers in Immunology, 2022)
Background: JMJD8 has recently been identified as a cancer-related gene, while current studies provided limited information. We aimed to clarify its roles and the potential mechanisms in pan-cancer. Methods: Pan-cancer bulk sequencing data and online web tools were applied to analyze JMJD8’s correlations with prognosis, genome instability, cancer stemness, DNA repair, and immune infiltration. Besides, single-cell datasets, SpatialDB database, and multiple fluorescence staining were used to validate the expression of JMJD8 in M2 macrophages. Further, we utilized ROCplotter and cMap web tool to analyze the therapeutic responses and screened JMJD8-targeted compounds, respectively, and we used AlphaFold2 and Discovery Studio to conduct JMJD8 homology modeling and molecular docking. Results: We first noticed that JMJD8 was an oncogene in many cancer types. High JMJD8 was associated with lower genome stability. We then found high JMJD8 correlated with high expression of mismatch repair genes, stemness, homologous repair gene signature, and chromatin remodeling signature in more than 9 cancers. ESTIMATE and cytokines analyses results presented JMJD8’s association with immunosuppression. Also, immune checkpoint CD276 was positively relevant to JMJD8. Subsequently, we validated JMJD8 as the M2 macrophage marker and showed its connection with other immunosuppressive cells and CD8+ T cell depression. Finally, JMJD8-targeted drugs were screened out and docked to JMJD8 protein. Conclusion: We found that JMJD8 was a novel oncogene, and it promoted immunosuppression and DNA repair. JMJD8 was highly associated with immune-checkpoint CD276 and was an M2 macrophage biomarker in many cancers. This study will reveal JMJD8’s roles in pan-cancer and its potential as a novel therapeutic target.